2017
DOI: 10.1177/0145482x1711100505
|View full text |Cite
|
Sign up to set email alerts
|

Procedures and Tools Used by Teachers When Completing Functional Vision Assessments with Children with Visual Impairments

Abstract: Introduction This study analyzed survey responses from 314 teachers of students with visual impairments regarding the tools and procedures used in completing functional vision assessments (FVAs). Methods Teachers of students with visual impairments in the United States and Canada completed an online survey during spring 2016. Results The majority of participants reported that they primarily assess pre-academic and academic students in kindergarten through 12th grade (K-12). More than 95% of all participants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 2 publications
2
20
0
Order By: Relevance
“…The authors found it surprising that both groups only rated 10 statements as extremely important in Round 1 (see Table 3). The authors were in agreement, however, with the importance of the 10 statements that have been corroborated by others including D’Andrea and Farrenkopf (2000); Erin and Paul (1996); Kaiser and Herzberg (2017); Lewis and Allman (2017); and Spungin et al (2017).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The authors found it surprising that both groups only rated 10 statements as extremely important in Round 1 (see Table 3). The authors were in agreement, however, with the importance of the 10 statements that have been corroborated by others including D’Andrea and Farrenkopf (2000); Erin and Paul (1996); Kaiser and Herzberg (2017); Lewis and Allman (2017); and Spungin et al (2017).…”
Section: Discussionsupporting
confidence: 81%
“…It may be challenging for university instructors to adequately prepare preservice teachers of students with visual impairments to complete FVAs for the heterogeneous student population. In a recent survey by Kaiser and Herzberg (2017), of 314 teachers, 29% reported that they had many gaps in their initial FVA training or that they did not receive training on content and procedures for conducting FVAs for academic students in kindergarten through 12th grade. In the same study, 51% of the teachers reported the same lack of training when asked about conducting FVAs for students under age 5 years or those with multiple disabilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout this article, “FVA data collection tools” are used to describe the checklists, informal protocols, forms, tables, and spreadsheets used by teachers during the FVA process. In a recent survey of 314 teachers of students with visual impairments in the United States and Canada, 29% ( n = 92) responded that there were significant gaps in their initial training regarding procedures for conducting FVAs (Kaiser & Herzberg, 2017). Additionally, 84% ( n = 264) responded that their employer does not require them to use any specific FVA tool, and 90% ( n = 284) reported that they have made their own or modified other tools (Kaiser & Herzberg, 2017).…”
mentioning
confidence: 99%
“…In a recent survey of 314 teachers of students with visual impairments in the United States and Canada, 29% ( n = 92) responded that there were significant gaps in their initial training regarding procedures for conducting FVAs (Kaiser & Herzberg, 2017). Additionally, 84% ( n = 264) responded that their employer does not require them to use any specific FVA tool, and 90% ( n = 284) reported that they have made their own or modified other tools (Kaiser & Herzberg, 2017). Similarly, in a survey of 233 teachers of students with visual impairments regarding the processes and materials used to complete FVAs, one half of the participants said they used tools that they had created, and 90% reported that a standardized tool would be helpful as long as it could be adapted to specific students (Shaw et al, 2009).…”
mentioning
confidence: 99%